The Effect of Top Management Involvement on Supply Chain Risk Management through Buyer-Supplier Relationship - Hotlan Siagian; Zeplin Jiwahusada Tarigan; Han Tae Hee (Jurnal Teknik Industri, 2018)
This paper aims to examine the role of the buyer-supplier relationship in improving the impact of top management involvement in the supply chain risk management. The study used 55 export-oriented manufacturing companies domiciled in East Java of Indonesia, and three respondents from top management level represented each company. Of 55, 44 companies have completed the questionnaires which means the response rate of 80%. Data collection used a questionnaire designed with a five-item Likert scale. Data analysis used the partial least square technique with Smart-PLS software version 3.0 to examine the hypotheses. The finding revealed that top management involvement affects supply chain risk management, top management involvement affects the buyer-supplier relationship, and buyer-supplier relationship affects supply chain risk management. The last finding is that buyer-supplier relationship empirically the effect of top management involvement. This paper paves the way for the manager in improving supply chain risk management by practicing top management involvement and development of a relationship with the supplier.